Mixed messages: resistance and reappropriation in rave culture - Ott, Brian L., author; Herman, Bill D., author; Western States Communication Association, publisher (Colorado State University. Libraries, 2003)
This essay concerns the dynamic tension between resistance and reappropriation in the youth subcultural practice of raving. We argue that the transgressive potential of underground rave culture lies primarily in its privileging of communion, which is facilitated along the intersecting axes of social space, authorship, the body, and the drug Ecstasy. The commodification of rave culture is demonstrated to be linked to a shifting consciousness reflected in changing attitudes toward Ecstasy, the relocation of dance culture into clubs, and the redefinition of the DJ as artist and superstar. A concluding section considers the implications of resistance and reappropriation in rave culture for social change and the exercise of power.
Brian Ott was a professor in the Department of Speech Communication at Colorado State University.
Keywords: social space; discourse; music; symbolic; embodied; logic of communion; power relationships